Growth Pattern of Thermophilic Bacterial Isolate SSA-16 from Sapan Sungai Aro Hot Springs - Suherman, Donny; Irdawati, Irdawati (Jurnal Serambi Biologi, 2024)
Thermophilic bacteria are a group of microorganisms that grow optimally at temperatures of more than 45°C and the general growth range is between 45°C to 80°C. To determine the growth pattern of thermophilic bacteria originating from the Sapan Sungai Aro hot springs, isolate SSA-16 was carried out by measuring the level of bacterial turbidity. The method used in this research is a descriptive approach using two replications (duplo). The isolate that is the focus is SSA-16. Bacteria were incubated for 24 hours at 2 hour intervals at a temperature of 50ºC and their growth was measured using a UV-Vis Spectrophotometer with a wavelength of 600 nm. The OD value is measured on a scale of 0 to 2. From the results of the tests that have been carried out, you can see the results of the Optical Density (OD) test to see the growth pattern of SSA-16 bacterial isolates using a UV-Vis spectrophotometer (600 nm) through several phases. The first phase is the lag phase which occurs from the 2nd to the 6th hour, the second is the exponential phase which occurs from the 8th to the 14th hour and reaches the highest average of 0.706 and in the next hour the bacterial growth is at the Stationary or bacterial growth can be declared stagnant.